Museum experience and satisfaction: moderating role of visiting frequency. Issue 2 (25th August 2020) - Preko, Alexander; Gyepi-Garbrah, Theophilus Francis; Arkorful, Helen; Akolaa, Andrews Adugudaa; Quansah, Fidelis
Abstract : Purpose: This paper aims at investigating how tourist experience elicits satisfaction and contributes to loyalty and willingness to pay more for a museum destination. The study also investigates the significant moderating role of visiting frequency on the relationship between satisfaction and willingness to pay more. Design/methodology/approach: The research was conducted with 385 tourists who visited the National Museum in Ghana and answered questions relating to experience, satisfaction, loyalty, and willingness to pay more. Structural equation modelling was used to test the relationships and effects of the adapted constructs. Findings: The results revealed the significant effects of tourist experience on satisfaction, as well as the significant effects of satisfaction on loyalty and willingness to pay more. In addition, a significant moderating effect of visiting frequency was reported on the relationship between satisfaction and tourist willingness to pay more. Research limitations/implications: The research is destination-specific. The application of the findings to other museums would demand a bigger sample size for generalisation to be made. Practical implications: Managers should develop strategies that promote museum tourist travelling experience, satisfaction, desire and choice, and thereby attract more tourists to museum sites. Originality/value: The research contributes to the growing literature on museum tourist experience as an important variable in promoting tourist satisfaction, loyalty, and tourist willingness to pay more.